Evaluation of water quality impact (water curing) on the compressive strength of bridge bearing non-shrink grout / Nur Farhana Norzelan, Sharifah Abdullah and Adiza Jamadin - Norzelan, Nur Farhana; Abdullah, Sharifah; Jamadin, Adiza (School of Civil Engineering, 2025)
Bridge bearings, crucial for connecting superstructures and substructures, rely on grouting to establish stability. This study investigates the impact of water quality on the compressive strength of non-shrink grout in bridge bearings. Cube tests, employing Fosroc Conbextra grout, were conducted to explore the effects of various water sources on both early and long-term strength. The goal is to enhance the durability of non-shrink grout by providing guidance on optimal water source selection. Grout cube specimens underwent curing in tap water, rainwater, river water, and wastewater and the water quality tests covered parameters such as appearance, temperature, pH, Total Dissolved Solids (TDS), salinity, conductivity, and Dissolved Oxygen (DO). Tap water and rainwater consistently demonstrated strength. Standard deviation analysis favored the reliability of rainwater over time compared to river water and wastewater. Despite its strength, tap water exhibited increased deviation from 7 to 28 days. This study emphasizes the crucial role of water quality in optimizing material performance, highlighting tap water for consistent strength and rainwater for reliability. Consideration of both strength and consistency is essential when selecting water curing methods for optimal material performance in construction and engineering.